American imperialism in the long nineteenth century
1 online resource (298 pages)
Keywords: This volume navigates the course of US imperialism between two major wars - the Mexican-American War (1846-1848) and the Spanish-American War (1898) - both of which saw significant US territorial expansion. However, these conflicts alone do not tell the whole story. Alongside the territorial acquisitions that followed the Treaty of Guadalupe Hidalgo (1848) this volume's sections also explore the so-called "winning of the West," the controversial Alaska Purchase of 1867, early US intrigue in the Caribbean, and the nation's expansion into the Pacific in the years leading up to the formal annexation of the Hawaiian Islands in 1898. This volume shows clearly that US expansion and imperialism took on a wide variety of guises in the second half of the nineteenth century, making even formal territorial expansion very difficult to characterise. The varied first-hand perspectives provided here also make it clear that the nature and purpose of "American imperialism" was always very much in the eye of the beholder.